2015
DOI: 10.3851/imp3007
|View full text |Cite
|
Sign up to set email alerts
|

Bull's Eye Maculopathy in an HIV-Positive Patient Receiving Ritonavir

Abstract: Retinal toxicity involving the macula as a complication of the antiretroviral protease inhibitor ritonavir has been described in a few cases. We report retinal pigment epitheliopathy involving the macula with a bull's eye pattern in a 36-year-old man with well-controlled HIV receiving ritonavir with gradually progressive bilateral vision loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…A review of the world literature disclosed 11 cases of ritonavir maculopathy reported between 2011 and 2019, to which we add our present case (patient 1). Results are compiled in Table 1 (1,(4)(5)(6)(7)(8)(9)(10)(11). All reported patients were male, the only female being our patient.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A review of the world literature disclosed 11 cases of ritonavir maculopathy reported between 2011 and 2019, to which we add our present case (patient 1). Results are compiled in Table 1 (1,(4)(5)(6)(7)(8)(9)(10)(11). All reported patients were male, the only female being our patient.…”
Section: Discussionmentioning
confidence: 94%
“…We searched the world literature for similar cases through PubMed and Google Scholar, using the terms "HIV, " "AIDS, " "ritonavir, " "didanosine, " "maculopathy, " "retinopathy, " "visual loss, " and "toxicity." Our literature search disclosed nine publications of retinal toxicity due to ritonavir between 2011 and 2020, for a total of 11 cases (1,(4)(5)(6)(7)(8)(9)(10)(11). Details are provided in Table 1.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the last few years, several case reports of pigmentary maculopathy, often in a Bull's-eye-like pattern, associated with ritonavir (a protease inhibitor) or efavirenz (a non-NRTI) use, have been reported [24][25][26][27][28][29]. These patients presented early with reduced vision due to the macular pathology [24][25][26][27][28][29]. Ritonavir toxicity is thought to be dose-related and related to phospholipidosis with crystalline deposits seen at the macula [25,26,29].…”
Section: Other Haart Retinal Toxicitymentioning
confidence: 99%
“…These patients presented early with reduced vision due to the macular pathology [24][25][26][27][28][29]. Ritonavir toxicity is thought to be dose-related and related to phospholipidosis with crystalline deposits seen at the macula [25,26,29]. The pathophysiology of efavirenzrelated toxicity remains unclear.…”
Section: Other Haart Retinal Toxicitymentioning
confidence: 99%
“…The case report titled “Bull's eye maculopathy in an HIV-positive patient receiving ritonavir” by Non et al [ 37 ] was excluded for the lack of sufficient clinical details and imaging.…”
mentioning
confidence: 99%